(untitled) (Journal of Forestry, 2024)
Non-timber forest products have become increasingly important in many fields such as medicine, pharmacy, industry, food, cosmetics, and perfumery, and are widely used today. Based on this, distribution models of three different non-timber forest products that are important in the Fethiye-Babadağ region were modeled, and potential distribution maps were obtained. Babadağ is one of Türkiye’s 9 hot spots. The MaxEnt method was used for modeling in the study. Fifteen topographic variables were generated for use in modeling. Climate data used in modeling were also obtained from the CHELSA database. As a result of the modeling process for the species, the AUC value of the model obtained for Arbutus andrachne L. was 0.954, for Origanum onites L. it was 0.822, and for Pistacia terebinthus L. 0.806. It was observed that the models were valid for all three species, based on the AUC values obtained. Potential distribution maps were obtained for each species according to these models. It is thought that these maps can play an effective and practical role in planning studies for each species.